Emotions as guardians of group norms: expressions of anger and disgust drive inferences about autonomy and purity violations. Issue 3 (3rd April 2019) - Heerdink, Marc W.; Koning, Lukas F.; van Doorn, Evert A.; van Kleef, Gerben A.
ABSTRACT: Other people's emotional reactions to a third person's behaviour are potentially informative about what is appropriate within a given situation. We investigated whether and how observers' inferences of such injunctive norms are shaped by expressions of anger and disgust. Building on the moral emotions literature, we hypothesised that angry and disgusted expressions produce relative differences in the strength of autonomy-based versus purity-based norm inferences. We report three studies (plus three supplementary studies) using different types of stimuli (vignette-based, video clips) to investigate how emotional reactions shape norms about potential norm violations (eating snacks, drinking alcohol), and contexts (groups of friends, a university, a company). Consistent with our theoretical argument, the results indicate that observers use others' emotional reactions not only to infer whether a particular behaviour is inappropriate, but also why it is inappropriate: because it primarily violates autonomy standards (as suggested relatively more strongly by expressions of anger) or purity standards (as suggested relatively more strongly by expressions of disgust). We conclude that the social functionality of emotions in groups extends to shaping norms based on moral standards.